Synthesis and Antibacterial Activity of Some Novel N,N-Di-Oxalamide Derivatives - Habash, Maha; Mohammad, Mohammad Yasin; Ayyash, Manal; Taha, Mutasem O (International Journal of Chemistry and Materials Research, 2015)
Novel N,N-di-oxalamide derivatives 1-6 were synthesized and characterized by the spectroscopic techniques. These derivatives showed good antibacterial activities against Gram-negative organism Escherichia coli and Gram-positive organisms Staphylococcus aureus and Bacillus subtilus. However, compounds 3 and 4 showed potent antibacterial activity against Gram-negative organism Escherichia coliand Gram-positive organism Staphylococcus aureus. In addition to that, we compared their antibacterial profiles with previously synthesized N,N-di-oxalamide derivatives 7-9. The new compounds showed superior antibacterial activities compared to moderate activities for 7-9.